Crystalline forms of pyrrolopyridine derivatives

By preparing the crystal form AD of the pyrrolopyridine derivative, the problems of low solubility and poor stability are solved, and high solubility and stability are achieved, making it suitable as a pharmaceutical raw material and suitable for treating acquired immunodeficiency syndrome.

CN120712264APending Publication Date: 2025-09-26ST PHARM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380094467.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-02-20
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing crystalline forms of pyrrolopyridine derivatives have problems of low solubility and poor stability, resulting in low bioavailability and difficulty in controlling drug release and blood drug concentration.

Method used

Four different crystalline forms A to D were prepared, and crystalline forms with excellent physicochemical properties were obtained through specific solvents and stirring methods, including the powder X-ray diffraction pattern and differential scanning calorimetry characteristic peaks of crystalline form A, ensuring the stability and solubility of the crystalline form.

Benefits of technology

Crystal form AD exhibits low hygroscopicity, excellent stability and high solubility, can maintain the stability and bioavailability of the drug for a long time, and is suitable as a pharmaceutical raw material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120712264A_ABST
    Figure CN120712264A_ABST
Patent Text Reader

Abstract

The invention relates to a polymorphic substance of a pyrrolopyridine derivative and a preparation method of the polymorphic substance. The polymorphic substance is used as a non-catalytic site integrase inhibitor. The novel polymorph of the present invention exhibits excellent non-hygroscopicity and stability, and thus is suitable for use in pharmaceutical formulations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field

[0001] The present invention relates to a crystalline form of a pyrrolopyridine derivative, which is a non-catalytic site integrase inhibitor. Furthermore, the present invention also relates to a method for preparing the crystalline form of the pyrrolopyridine derivative. [Background Technology]

[0002] Acquired immunodeficiency syndrome (AIDS) is caused by infection with the human immunodeficiency virus (HIV). Enzyme inhibitors have been developed for the treatment of AIDS based on the mechanism of action of HIV. Based on their site of action, enzyme inhibitors are categorized as nucleoside reverse transcriptase inhibitors (NRTIs), protease inhibitors (PIs), fusion inhibitors, and integrase inhibitors. Due to the side effects, drug interactions, and drug resistance associated with reverse transcriptase inhibitors, protease inhibitors, and fusion inhibitors, the development of integrase inhibitors is being actively pursued.

[0003] Integrase inhibitors are classified according to their mechanism of action as catalytic site inhibitors and non-catalytic site inhibitors. Raltegravir is a representative catalytic site integrase inhibitor. While Zeger DeBessel et al. introduced the mechanism of non-catalytic site integrase inhibition (Fletcher-Christin, Zeger DeBessel et al., Nature Chemical Biology, 2010, Vol. 6, 442), no relevant drugs have yet been successfully developed.

[0004] However, raltegravir, a catalytic site integrase inhibitor, has also been found to exhibit drug resistance. In HIV infection, if medication is interrupted, latent HIV may reactivate and develop drug resistance, rendering previously taken medication ineffective. Therefore, efforts are underway to develop non-catalytic site integrase inhibitors as a solution to drug resistance. In particular, pyrrolopyridine derivatives represented by the following chemical formula (I) are known non-catalytic site integrase inhibitors:

[0005] [Chemical Formula I]

[0006]

[0007] When designing a suitable dosage form during drug production, choosing the physical state of the drug substance, i.e., crystalline or amorphous, is crucial. However, crystalline raw materials have low solubility, which can result in low bioavailability per unit weight, while amorphous forms are unstable, making drug release and blood concentration control difficult.

[0008] Therefore, it is necessary to develop a new crystal form of a pyrrolopyridine derivative represented by the above chemical formula I to simultaneously solve these problems and exhibit excellent physicochemical properties. [Summary of the invention]

Technical Issues

[0009] The object of the present invention is to provide a crystal form of a pyrrolopyridine derivative and a preparation method thereof, wherein the crystal form has excellent non-hygroscopicity and stability and can improve solubility and bioavailability.

Technical Solution

[0010] To achieve the above-mentioned object, the present inventors conducted research and made efforts to prepare the following crystal forms A to D, and confirmed that all of these crystal forms exhibited excellent effects, thereby completing the present invention.

[0011] Crystal form A and preparation method thereof

[0012] The present invention provides a crystalline form A of the compound represented by the following chemical formula I, whose powder X-ray diffraction pattern includes peaks at diffraction angles (2θ±0.2°) of 9.26°, 10.47°, 12.76°, 14.70°, 15.83°, and 16.61°:

[0013] [Chemical Formula I]

[0014]

[0015] According to one embodiment of the present invention, the powder X-ray diffraction pattern of the crystalline form A may further include at least one peak at a diffraction angle (2θ±0.2°) of 17.57°, 18.50°, 20.15°, 21.06°, 22.17°, 23.98° or 27.05°.

[0016] According to one embodiment of the present invention, the powder X-ray diffraction pattern of the crystalline form A may also include at least one peak at a diffraction angle (2θ±0.2°) of 8.02°, 8.39°, 8.72°, 13.92°, 16.40°, 17.79°, 19.33°, 23.38°, 24.36°, 24.90°, 25.59°, 25.99°, 26.70°, 27.85°, 29.37°, 29.98°, 30.77° or 31.59°.

[0017] According to one embodiment of the present invention, when the temperature rise rate of the crystal form A is 10° C. / min, differential scanning calorimetry (DSC) may have an endothermic transition peak at 208-215° C.

[0018] In addition, the present invention also provides a method for preparing the crystalline form A. Specifically, the above-mentioned preparation method may include the following steps:

[0019] (A-1) adding the compound represented by the above Chemical Formula I to toluene, ethyl acetate or isopropyl alcohol, followed by stirring; and

[0020] (A-2) The obtained solid was filtered and dried.

[0021] Crystal form B and preparation method thereof

[0022] The present invention provides a crystalline form B of the compound represented by the above chemical formula I, whose powder X-ray diffraction pattern includes peaks at diffraction angles (2θ±0.2°) of 9.24°, 12.79°, 15.43°, 16.32°, 17.83° and 19.35°.

[0023] According to one embodiment of the present invention, the powder X-ray diffraction pattern of the crystalline form B may further include at least one peak at a diffraction angle (2θ±0.2°) of 20.18°, 23.35°, 23.84°, 24.46°, 26.03°, 29.66° or 30.53°.

[0024] According to one embodiment of the present invention, the powder X-ray diffraction pattern of the crystalline form B may further include at least one peak at a diffraction angle (2θ±0.2°) of 7.94°, 10.03°, 11.65°, 14.63°, 16.80°, 17.55°, 18.63°, 21.58°, 22.67°, 23.62°, 25.29°, 27.15°, 28.13°, 29.38°, 30.68°, 31.61°, 32.05°, 33.04°, 34.41°, 35.50° or 36.26°.

[0025] According to one embodiment of the present invention, when the temperature rise rate of the crystal form B is 10° C. / min, differential scanning calorimetry (DSC) may have an endothermic transition peak at 213-218° C.

[0026] In addition, the present invention also provides a method for preparing the crystal form B. Specifically, the above preparation method may include the following steps:

[0027] (B-1) adding the compound represented by the above Chemical Formula I to ethanol, followed by stirring; and

[0028] (B-2) The obtained solid was filtered and dried.

[0029] Crystal form C and preparation method thereof

[0030] The present invention provides a crystalline form C of the compound represented by the above chemical formula I, whose powder X-ray diffraction pattern includes peaks at diffraction angles (2θ±0.2°) of 7.62°, 8.61°, 10.10°, 12.06°, 13.52° and 15.72°.

[0031] According to one embodiment of the present invention, the powder X-ray diffraction pattern of the crystalline form C may further include at least one peak at a diffraction angle (2θ±0.2°) of 17.35°, 18.73°, 19.62°, 22.60°, 23.50° or 25.57°.

[0032] According to one embodiment of the present invention, the powder X-ray diffraction pattern of the crystalline form C may further include at least one peak at a diffraction angle (2θ±0.2°) of 9.23°, 9.73°, 11.36°, 12.85°, 15.37°, 16.16°, 17.85°, 20.34°, 21.00°, 23.96°, 24.37°, 25.21°, 26.24°, 27.33°, 27.84°, 29.70°, 30.32°, 31.08°, 33.94° or 35.18°.

[0033] According to one embodiment of the present invention, when the temperature rise rate of the crystalline form C is 10° C. / min, differential scanning calorimetry (DSC) may have endothermic transition peaks at 124-143° C. and 207-213° C.

[0034] In addition, the present invention also provides a method for preparing the crystal form C. Specifically, the above preparation method may include the following steps:

[0035] (C-1) adding the compound represented by the above Chemical Formula I to methanol, followed by stirring; and

[0036] (C-2) The obtained solid was filtered and dried.

[0037] Crystal form D and preparation method thereof

[0038] The present invention provides a crystalline form D of the compound represented by the above chemical formula I, whose powder X-ray diffraction pattern includes peaks at diffraction angles (2θ±0.2°) of 8.70°, 11.42°, 13.62°, 15.51°, 16.70° and 21.58°.

[0039] According to one embodiment of the present invention, the powder X-ray diffraction pattern of the crystalline form D may further include at least one peak at a diffraction angle (2θ±0.2°) of 7.52°, 9.37°, 9.89°, 18.59° or 23.84°.

[0040] According to one embodiment of the present invention, the powder X-ray diffraction pattern of the crystalline form D may further include at least one peak at a diffraction angle (2θ±0.2°) of 8.24°, 10.72°, 12.02°, 12.38°, 15.01°, 15.93°, 17.95°, 19.91°, 20.62°, 21.29°, 22.71° or 27.10°.

[0041] According to one embodiment of the present invention, when the temperature rise rate of the crystal form D is 10° C. / min, differential scanning calorimetry (DSC) may have an endothermic transition peak at 204-209° C.

[0042] In addition, the present invention also provides a method for preparing the crystal form D. Specifically, the above preparation method may include the following steps:

[0043] (D-1) adding the compound represented by the above chemical formula I to acetone and water, followed by stirring under reflux;

[0044] (D-2) filtering insoluble matter, adding water, and stirring; and

[0045] (D-3) The obtained solid was filtered and dried. Beneficial effects

[0046] The crystalline form of the present invention may have low hygroscopicity, excellent stability under accelerated and long-term storage conditions, and may stably maintain the content without change over a long period of time, which is advantageous for pharmaceutical preparations.

[0047] Furthermore, the crystalline form of the present invention may have high solubility and bioavailability, and thus may be usefully used as a pharmaceutical raw material.

Brief Description of the Drawings

[0048] Figure 1 The powder X-ray diffraction (PXRD) results of Form A of Example 1 of the present invention are shown.

[0049] Figure 2 The differential scanning calorimetry (DSC) thermogram results of Form A of Example 1 of the present invention are shown.

[0050] Figure 3 The powder X-ray diffraction (PXRD) results of Form B of Example 2 of the present invention are shown.

[0051] Figure 4 The differential scanning calorimetry (DSC) thermogram results of Form B of Example 2 of the present invention are shown.

[0052] Figure 5 The powder X-ray diffraction (PXRD) results of Form C of Example 3 of the present invention are shown.

[0053] Figure 6 The differential scanning calorimetry (DSC) thermogram results of Form C of Example 3 of the present invention are shown.

[0054] Figure 7 The powder X-ray diffraction (PXRD) results of Form D of Example 4 of the present invention are shown.

[0055] Figure 8 The differential scanning calorimetry (DSC) thermogram results of Form D of Example 4 of the present invention are shown. Best Practice

[0056] Hereinafter, the present invention will be described in more detail by way of examples and experimental examples for ease of understanding. However, the following examples and experimental examples are only intended to illustrate the present invention, and the content of the present invention is not limited to these examples. These examples and experimental examples of the present invention are provided to more fully illustrate the present invention to those of ordinary skill in the art.

[0057] Unless otherwise specified, the following reagents and solvents were purchased from Sigma-Aldrich Korea, TCI, and Ooi Chemical & Metals, and HLPC was measured using 1000 series from Agilent Technologies.

[0058] In addition, various solid forms of (S)-2-(tert-butoxy)-2-(4-(4-chlorophenyl)-2,3,6-trimethyl-1-((1-methyl-1H-pyrazol-4-yl)methyl)-1H-pyrrolo[2,3-b]pyridin-5-yl)acetic acid prepared by the following examples were identified by X-ray diffraction patterns using X-ray diffraction and differential scanning calorimetry (DSC) patterns using DSC.

[0059] Specifically, powder X-ray diffraction analysis was performed using a Bruker D8 focusing model equipped with a rotometer and a solid-state detector, using Cu-Kα radiation under the conditions of an analysis range of 5°-50°, a step length of 0.020°, and a step time of 171.6 seconds. In addition, differential scanning calorimetry (DSC) measurements were performed using a DSC3 from Mettler-Toledo at a temperature of 50-300°C at a heating rate of 10°C / min.

[0060] Preparation Example: Preparation of (S)-2-(tert-butoxy)-2-(4-(4-chlorophenyl)-2,3,6-trimethyl-1-((1-methyl-1H-pyrazol-4-yl)methyl)-1H-pyrrolo[2,3-b]pyridin-5-yl)acetic acid.

[0061] [Chemical Formula I]

[0062]

[0063] (S)-2-(tert-Butoxy)-2-(4-(4-chlorophenyl)-2,3,6-trimethyl-1-((1-methyl-1H-pyrazol-4-yl)methyl)-1H-pyrrolo[2,3-b]pyridin-5-yl)acetate (13.5 g, 25.8 mmol) was diluted in 108 mL of tetrahydrofuran and 27 mL of methanol. Sodium hydroxide (3.1 g, 77.4 mmol) was added and stirred at 40-45 ° C for 4 hours. After the reaction was completed, the resulting mixture was concentrated under reduced pressure, and 120 mL of dichloromethane and 60 mL of purified water were added. The reaction mixture was cooled to 0-5 ° C, and the pH was adjusted to 4.5-5.0 with 2N-hydrochloric acid solution. The organic layer was separated and washed with 60 mL of purified water, then dried over anhydrous sodium sulfate, filtered, and concentrated under reduced pressure. To the residue was added 30 mL of acetonitrile, and the mixture was cooled to 5-10° C. and stirred for 3 hours. The precipitated crystals were filtered and dried under reduced pressure to obtain the title compound (9.25 g, 72%, ee: 99%) as an off-white solid.

[0064] Example 1: Preparation of Form A.

[0065] According to Table 1 below, 1 g of (S)-2-(tert-butoxy)-2-(4-(4-chlorophenyl)-2,3,6-trimethyl-1-((1-methyl-1H-pyrazol-4-yl)methyl)-1H-pyrrolo[2,3-b]pyridin-5-yl)acetic acid prepared in the above-described Preparation Example of the present invention was added to various solvents and then stirred at room temperature overnight. The resulting solid was filtered and dried in a hot air dryer at 50°C to obtain Form A.

[0066] [Table 1]

[0067]

[0068] The powder X-ray diffraction (PXRD) peaks and differential scanning calorimetry (DSC) endothermic peaks of the obtained solid were analyzed, and the results were as follows: Figure 1 and 2 shown.

[0069] like Figure 1 It was confirmed that the solid compound showed main peaks at 2θ (±0.2°) values ​​of 9.26°, 10.47°, 12.76°, 14.70°, 15.83° and 16.61°.

[0070] also, Figure 2 It was confirmed that when the heating rate was 10°C / min, the solid compound showed an endothermic transition peak at 208-215°C by differential scanning calorimetry (DSC).

[0071] Example 2: Preparation of Form B.

[0072] 1 g of (S)-2-(tert-butoxy)-2-(4-(4-chlorophenyl)-2,3,6-trimethyl-1-((1-methyl-1H-pyrazol-4-yl)methyl)-1H-pyrrolo[2,3-b]pyridin-5-yl)acetic acid prepared in the above-mentioned preparation example of the present invention was added to ethanol (5 mL, 5V), and then stirred at room temperature overnight. The resulting solid was filtered and dried in a hot air dryer at 50°C to obtain Form B (0.71 g, 71%).

[0073] The powder X-ray diffraction (PXRD) peaks and differential scanning calorimetry (DSC) endothermic peaks of the obtained solid were analyzed, and the results were as follows: Figure 3 and 4 shown.

[0074] like Figure 3 It was confirmed that the solid compound showed main peaks at 2θ (±0.2°) values ​​of 9.24°, 12.79°, 15.43°, 16.32°, 17.83°, and 19.35°.

[0075] Further, Figure 4 It was confirmed that when the heating rate was 10°C / min, the solid compound showed an endothermic transition peak at 213-218°C by differential scanning calorimetry (DSC).

[0076] Example 3. Preparation of Form C

[0077] 1 g of (S)-2-(tert-butoxy)-2-(4-(4-chlorophenyl)-2,3,6-trimethyl-1-((1-methyl-1H-pyrazol-4-yl)methyl)-1H-pyrrolo[2,3-b]pyridin-5-yl)acetic acid prepared in the above-mentioned preparation example of the present invention was added to methanol (5 mL, 5V), and then stirred at room temperature overnight. The resulting solid was filtered and dried in a hot air dryer at 50°C to obtain Form C (0.71 g, 76%).

[0078] The powder X-ray diffraction (PXRD) peaks and differential scanning calorimetry (DSC) endothermic peaks of the obtained solid were analyzed, and the results were as follows: Figure 5 and 6 shown.

[0079] like Figure 5 It was confirmed that the solid compound showed main peaks at 2θ (±0.2°) values ​​of 7.62°, 8.61°, 10.10°, 12.06°, 13.52° and 15.72°.

[0080] Further, Figure 6Differential scanning calorimetry (DSC) confirmed that the solid compound exhibited an endothermic transition peak at 124-143°C when the heating rate was 10°C / min. The exothermic peak observed after the endothermic (melting) peak indicated crystal precipitation. Following crystal precipitation (exothermic peak), an endothermic peak was observed again at 206-213°C.

[0081] Example 4. Preparation of Form D

[0082] 1 g of (S) -2- (tert-butoxy) -2- (4- (4-chlorophenyl) -2,3,6-trimethyl -1- ( (1-methyl -1H- pyrazol-4-yl) methyl) -1H- pyrrolo [2,3-b] pyridin-5-yl) prepared in the above-mentioned preparation example of the present invention was diluted in a mixed solvent of 10 mL of acetone and 0.4 mL of purified water, and then stirred under reflux for 1 hour. The undissolved insoluble matter was filtered out, and 10 mL of purified water was added dropwise to the filtrate for 10 minutes with stirring. The resulting solid was stirred at room temperature for 30 minutes, filtered, and dried in a hot air dryer at 50 ° C to obtain Form D (0.91 g, 91%).

[0083] The powder X-ray diffraction (PXRD) peaks and differential scanning calorimetry (DSC) endothermic peaks of the solid were analyzed, and the results were as follows: Figure 7 and 8 shown.

[0084] like Figure 7 It was confirmed that the solid compound showed main peaks at 2θ (±0.2°) values ​​of 8.70°, 11.42°, 13.62°, 15.51°, 16.70° and 21.58°.

[0085] also, Figure 8 It was confirmed that when the heating rate was 10°C / min, the solid compound showed a differential scanning calorimetry (DSC) endothermic transition peak at 204-209°C.

[0086] Experimental Example 1. Hygroscopicity (DVS) measurement experiment

[0087] The hygroscopicity test was performed on the crystal form prepared in the examples of the present invention.

[0088] a. Equipment used in the experiment

[0089] -Model Name: DVS Intrinsic (Surface Measurement System)

[0090] -Specification

[0091] Temperature range: 20-40℃

[0092] Temperature stability: ±0.2℃

[0093] Humidity range: 0-98% relative humidity (RH)

[0094] RH accuracy: ±1% RH

[0095] Typical gas (nitrogen + water vapor) flow rate: 200 sccm

[0096] Sample chamber: 40mm wide x 50mm deep x 50mm high

[0097] Heating system: Peltier+Cartridge

[0098] b. Sample information

[0099] Experiments were conducted on the crystal forms of the above examples.

[0100] c. Experimental conditions

[0101] - Temperature: 25℃

[0102] -Humidity range: starting from 0% and up to 95%

[0103] -Solvent: Water

[0104] d. Experimental methods

[0105] A predetermined amount (10-20 mg) of the crystal form prepared in each example was placed on a sample tray in a sample box, and nitrogen was purged for 1 hour through a tube connected to the sample chamber to remove moisture from the sample chamber and the sample. The humidity in the sample chamber was controlled by adjusting the water vapor, and the target relative humidity was gradually increased from 0% to about 10% to measure the moisture content of the crystal form. The mass of each sample was measured (from 0% RH to 95% RH), and the change in sample weight caused by increasing or decreasing humidity was plotted as a graph.

[0106] The changes in moisture content of the crystal forms according to the examples are shown in Table 2 below.

[0107] [Table 2]

[0108]

[0109] The analysis results, as shown in Table 2 above, show that the crystalline form of the present invention has excellent non-hygroscopicity and the moisture content has almost no change. This shows that the crystalline form of the present invention is superior in the formulation throughout the entire process of manufacturing, storage and formulation of the active ingredient.

[0110] Experimental Example 2: Accelerated stability test.

[0111] The crystalline powder of each example of the present invention was double-packed in a PE bag and triple-packed in an aluminum bag and placed at 40±2°C, RH 75±5% for 0 and 6 months, and then the impurities were measured using HPLC. The results are shown in Table 3 below.

[0112] [Table 3]

[0113]

[0114] The results in Table 3 above confirm that the crystal form of the present invention remains crystalline, with no significant changes in the amount of related substances observed. Therefore, it can be understood that the crystal form of the present invention can stably maintain high purity for up to 6 months under accelerated conditions, exhibiting excellent stability, minimal change in moisture content, and significantly low hygroscopicity.

[0115] Experimental Example 3: Long-term stability test.

[0116] The crystalline powder of each example of the present invention was double-packed in a PE bag and triple-packed in an aluminum bag and stored at 25±2°C, RH 60±5% for 0 and 12 months, and then impurities were measured using HPLC. The results are shown in Table 4 below.

[0117] [Table 4]

[0118]

[0119] The results in Table 4 above confirm that the crystal form of the present invention remains crystalline, with no significant changes in the relevant substances and amounts observed. Therefore, it can be understood that the crystal form of the present invention can stably maintain high purity for 12 months, exhibiting excellent stability, minimal change in moisture content, and significantly low hygroscopicity.

Claims

1. A crystalline form A of a compound represented by the following chemical formula I, wherein the powder X-ray diffraction pattern thereof comprises peaks at diffraction angles (2θ±0.2°) of 9.26°, 10.47°, 12.76°, 14.70°, 15.83°, and 16.61°: [Chemical Formula I] 2. The crystalline form A according to claim 1, wherein the powder X-ray diffraction pattern further comprises at least one peak at a diffraction angle (2θ±0.2°) of 17.57°, 18.50°, 20.15°, 21.06°, 22.17°, 23.98° or 27.05°.

3. The crystalline Form A according to claim 2, wherein the powder X-ray diffraction pattern further comprises at least one peak at a diffraction angle (2θ±0.2°) of 8.02°, 8.39°, 8.72°, 13.92°, 16.40°, 17.79°, 19.33°, 23.38°, 24.36°, 24.90°, 25.59°, 25.99°, 26.70°, 27.85°, 29.37°, 29.98°, 30.77° or 31.59°.

4. The crystalline form A according to claim 1, wherein the crystalline form A has an endothermic transition peak at 208-215°C by differential scanning calorimetry (DSC) when the heating rate is 10°C / min.

5. A method for preparing the crystalline form A of the compound represented by Chemical Formula I according to claim 1-4, comprising: (A-1) adding a compound represented by the following chemical formula (I) to toluene, ethyl acetate or isopropyl alcohol, followed by stirring; and (A-2) filtering and drying the obtained solid; [Chemical Formula I] 6. A crystalline form B of the compound represented by the following chemical formula I, whose powder X-ray diffraction pattern includes peaks at diffraction angles (2θ±0.2°) of 9.24°, 12.79°, 15.43°, 16.32°, 17.83° and 19.35°: [Chemical Formula I] 7. Form B according to claim 6, wherein the powder X-ray diffraction pattern further comprises at least one peak at a diffraction angle (2θ±0.2°) of 20.18°, 23.35°, 23.84°, 24.46°, 26.03°, 29.66° or 30.53°.

8. Form B according to claim 7, wherein the powder X-ray diffraction pattern further comprises at least one peak at a diffraction angle (2θ±0.2°) of 7.94°, 10.03°, 11.65°, 14.63°, 16.80°, 17.55°, 18.63°, 21.58°, 22.67°, 23.62°, 25.29°, 27.15°, 28.13°, 29.38°, 30.68°, 31.61°, 32.05°, 33.04°, 34.41°, 35.50° or 36.26°.

9. The crystalline form B according to claim 6, wherein the crystalline form B has an endothermic transition peak at 213-218°C by differential scanning calorimetry (DSC) when the heating rate is 10°C / min.

10. A method for preparing Form B of the compound of Formula I according to claim 6-9, comprising: (B-1) adding a compound represented by the following chemical formula I to ethanol, followed by stirring; and (B-2) filtering and drying the obtained solid; [Chemical Formula I] 11. A crystalline form C of the compound represented by the following chemical formula I, whose powder X-ray diffraction pattern includes peaks at diffraction angles (2θ±0.2°) of 7.62°, 8.61°, 10.10°, 12.06°, 13.52° and 15.72°: [Chemical Formula I] 12. The crystalline Form C according to claim 11, wherein the powder X-ray diffraction pattern further comprises at least one peak at a diffraction angle (2θ±0.2°) of 17.35°, 18.73°, 19.62°, 22.60°, 23.50° or 25.57°.

13. The crystalline Form C according to claim 12, wherein the powder X-ray diffraction pattern further comprises at least one peak at a diffraction angle (2θ±0.2°) of 9.23°, 9.73°, 11.36°, 12.85°, 15.37°, 16.16°, 17.85°, 20.34°, 21.00°, 23.96°, 24.37°, 25.21°, 26.24°, 27.33°, 27.84°, 29.70°, 30.32°, 31.08°, 33.94°, or 35.18°.

14. The crystalline form C according to claim 11, wherein the crystalline form C has endothermic transition peaks at 124-143°C and 207-213°C by differential scanning calorimetry (DSC) when the heating rate is 10°C / min.

15. A method for preparing Form C of the compound of Formula I according to claims 11-14, comprising: (C-1) adding a compound represented by the following chemical formula I to methanol, followed by stirring; and (C-2) filtering and drying the obtained solid; [Chemical Formula I] 16. A crystalline form D of the compound represented by the following chemical formula I, whose powder X-ray diffraction pattern includes peaks at diffraction angles (2θ±0.2°) of 8.70°, 11.42°, 13.62°, 15.51°, 16.70° and 21.58°: [Chemical Formula I] 17. The crystalline Form D according to claim 16, wherein the powder X-ray diffraction pattern further comprises at least one peak at a diffraction angle (2θ±0.2°) of 7.52°, 9.37°, 9.89°, 18.59° or 23.84°.

18. The crystalline Form D according to claim 17, wherein the powder X-ray diffraction pattern further comprises at least one peak at a diffraction angle (2θ±0.2°) of 8.24°, 10.72°, 12.02°, 12.38°, 15.01°, 15.93°, 17.95°, 19.91°, 20.62°, 21.29°, 22.71° or 27.10°.

19. The crystalline form D according to claim 16, wherein the crystalline form D has an endothermic transition peak at 204-209°C when the heating rate is 10°C / min by differential scanning calorimetry (DSC).

20. A method for preparing the crystalline form D of the compound of formula I according to claims 16-19, comprising: (D-1) adding a compound represented by the following chemical formula (I) to acetone and water, followed by stirring under reflux; (D-2) filtering insoluble matter, adding water, and stirring; and (D-3) filtering and drying the obtained solid; [Chemical Formula I] 21. An antiviral pharmaceutical composition comprising the crystalline form A according to claims 1-4, the crystalline form B according to claims 6-9, the crystalline form C according to claims 11-14, or the crystalline form D according to claims 16-19.

22. The antiviral pharmaceutical composition according to claim 21, wherein the composition is used to fight human immunodeficiency virus (HIV).